2016
DOI: 10.1007/s41104-016-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Injection strategies for low HC raw emissions in SI engines with CNG direct injection

Abstract: The energy source natural gas represents an attractive alternative fuel for SI engines due to its suitable chemical properties. But the lower performance yield and the insufficient infrastructure lead to a rejection by the customer. One approach to gain acceptance is the improvement of the driveability of the natural gas-powered vehicles. Direct injection of CNG is a technology with potential to achieve this objective. Nevertheless, the combustion concept has high requirements on injection system and mixture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Though not depicted here, similar trends are observed at other tested engine speeds and loads up to 9 bar BMEP. Note that CO emissions increase when SOI advances from 240 to 280 deg bTDCFire (Figure 4e) despite the increased mixing time, which was also observed in previous studies [15,36]. These other studies reasoned that the early start of fuel injection likely disrupts the incoming air stream, leading to rich pockets that increase CO emissions.…”
Section: Methodology Of Engine-out Total Co2 Equivalent Emissions Cal...supporting
confidence: 78%
See 1 more Smart Citation
“…Though not depicted here, similar trends are observed at other tested engine speeds and loads up to 9 bar BMEP. Note that CO emissions increase when SOI advances from 240 to 280 deg bTDCFire (Figure 4e) despite the increased mixing time, which was also observed in previous studies [15,36]. These other studies reasoned that the early start of fuel injection likely disrupts the incoming air stream, leading to rich pockets that increase CO emissions.…”
Section: Methodology Of Engine-out Total Co2 Equivalent Emissions Cal...supporting
confidence: 78%
“…DI CNG has the potential to overcome the limitations of PFI systems by mitigating the loss of volumetric efficiency. Furthermore, DI CNG allows for improved scavenging and in-cylinder, multiple injection capability as opposed to CNG PFI technology [2,9]. Husted et al [10] showed that up to two-thirds of the torque deficiency between GDI and PFI CNG operation can be recovered with DI CNG.…”
Section: Introductionmentioning
confidence: 99%
“…Injection pressure was found to have minimal effect on the emission levels of HC. Injection timing was paramount in forming the proper mixture formation to achieve a low HC emissions [52].…”
Section: High Pressure Direct Injection (Hpdi)mentioning
confidence: 99%
“…Basic conical injector flow schematic[64].Based on calculations using Equations 4-6[52], I found that the ideal injection pressure window to maintain choked (or maximum) injection flow occurred from 180 to 65 CAD BTDC for an injection pressure of 275 kPa gauge. For an injection pressure of 137 kPa gauge this pressure window reduced into 180 to 83.5 CAD BTDC.…”
mentioning
confidence: 99%